SAT0028 PERIPHERAL BLOOD REGULATORY T-LYMPHOCYTES OF PATIENTS WITH RHEUMATOID ARTHRITIS BEFORE AND AFTER ALFACALCIDOL THERAPY. (June 2019) - Radnic, Tatjana; Pasalic, Katarina; Bukilica, Mirjana Sefik; Markovic, Ivanka; Damjanov, Nemanja; Vojinovic, Jelena
Abstract : Background: The identification of regulatory T cells (Treg) changed the Th1/Th2 dihotomy response in the pathogenesis of autoimmune diseases. Treg suppresses various autoreactive responses and maintain auto-tolerance in the immune system. The vitamin D receptor is widely expressed in immune cells, including monocytes, macrophages, dendritic cells, NK cells, and T and B lymphocytes, and plays an important role in the regulation of the immune system, and in the modulation of immunologically mediated diseases. Alfacalcidol, a synthetic analogue of hormone D, used in the prevention and treatment of osteoporosis, but the last results indicate its potential therapeutic effects in autoimmune diseases. Objectives: Assess the presence of regulatory T cells in patients with active rheumatoid arthritis (RA)patients before and after 12 weeks of 2 mcg of alfacalcidol administration daily, and in healthy controls. Methods: The study included 16 patients with RA, both sexes, with active disease (DAS 28 (SE)> 3.2, despite therapy with LMTBs for at least a month and 20 healthy volunteers (the same distribution of sex and age) - a control group of healthy subjects. In addition to their regular LMTB therapy, patients with RA received daily alfacalcidol (2mcg/day) for 12 weeks. Phenotypic characterization of peripheral blood lymphocytes was performed by direct and indirect immunofluorescence technique using the BD FACS Aria III flow cytofluorimeter. Descriptive and analytical statistics were used in data analysis. Results: A small percentage of activated Treg cells (HLA-DR + compared to total T-reg lymphocytes) in the peripheral blood of patients with active RA was detected in the Treg lymphocytes in relation to the control group of healthy subjects, which is close to the statistical significance level (4.76% versus 6.5% = 0.07). In contrast, the percentage of total Treg cells (Treg versus total CD4 +) was slightly higher in patients compared to a healthy control group (7.6% versus 5.85%, p = 0.129). After a 12-week treatment with alfacalcidol in patients with RA, an increase in the percentage of activated Treg cells (HLA-DR + relative to total T-reg lymphocytes) was observed in relation to the values detected at the beginning of the study, up to the level recorded in the group of healthy controls 6.13% vs. 4.76%, p = 0.219). Conclusion: It is believed that functional blockade of Treg cells plays the most important role in RA immunopathogenesis, most likely due to inhibition of their function by proinflammatory cytokines, due to an increase in the number of activated effector T cells, or perhaps due to the fact that some completely differentiated T reg cells can be very unstable. Our results are in favor of the potential immunomodulatory effect of alfacalcidol in autoimune Th1/Th17-mediated diseases. Disclosure of Interests: Tatjana Radnic: None declared, Katarina Pasalic: None declared, Mirjana Sefik Bukilica: None declared, Ivanka Markovic: None declared, Nemanja Damjanov Grant/research support from: AbbVie, Pfizer and Roche, Consultant for: Abbvie, Gedeon Richter, Merck, Novartis, Pfizer and Roche., Speakers bureau: Abbvie, Gedeon Richter, Merck, Novartis, Pfizer and Roche., Jelena Vojinovic: None declared